ANALISIS KINERJA ANGGARAN MENGUNAKAN METODE VALUE FOR MONEY PADA PEMERINTAH DAERAH PROVINSI NUSA TENGGARA TIMUR PERODE 2017-2021 - Tameon, Alwin Fedianto; Rafael, Sarinah Joyce M.; Ga, Linda Lomi (Universitas Nusa Cendana, 2023)
The aim of this study is to determine the performance of the budget for the Regional Government of East Nusa Tenggara Province for five fiscal years (2017-2021) with the concept of measuring value for money which consists of three main elements, namely economy, efficiency and effectiveness. The type of research used in this study is to use a qualitative descriptive method. Data collection techniques used in this research are documentation techniques and literature assessment techniques. The data processed in this study is a report on the budget realization of the periode year from 2017-2021 for the Province of East Nusa Tenggara. The data analysis technique used in this study are using economic ratios, efficiency ratios, and effectiveness ratios. The results of this study indicate that the financial performance of the Government of East Nusa Tenggara Province for the 2017-2021 for economic ratios is in the quite economical category, and efficiency ratios are in the efficient category, while for effectiveness ratios are in the effective category. The results of this analysis explain that the Regional Government of East Nusa Tenggara Province is good at managing its finances